The Relative Impact of Income and Consumption Taxes. (IMF Working Papers; Working Paper, 1988)
This paper examines the possibility of ascertaining the welfare changes that occur when a consumption tax replaces an equal-yield income tax. It finds that those with saving/income ratios greater than the social saving/income ratio under the income tax will surely benefit and those with ratios smaller than the social rate under the consumption tax will surely be harmed. These conditions are in each case sufficient to guarantee these results-but not necessary. Some can be better off and others worse off without these conditions holding. It is thus theoretically impossible to predict the welfare effects on many taxpayers of the tax shift from the observable data.